What are the future directions for microplastics characterization? A regex-llama data mining approach for identifying emerging trends - FERNANDO GOMES; SHEKHAR BHANSALI; FABÍOLA MARANHÃO; VIVIANE VALLADÃO; KARINE VELASCO (Anais da Academia Brasileira de Ciências, 2025)
Abstract This study introduces a hybrid method to identify and analyze techniques for microplastic analysis. We improve the detection and understanding of both established and new techniques by integrating regex-based pattern detection with the Llama 3.2:3b language model. Techniques like Raman and FTIR spectroscopy are explored alongside advanced tools, such as X-ray Photoelectron Spectroscopy (XPS) and Surface-Enhanced Raman Spectroscopy (SERS). This combination enhances the accuracy and speed of identifying complex terminology related to microplastics research. Data analysis and visualization were conducted using VOSDataAnalyzer and VOSviewer, allowing us to map connections and trends within a network of related terms. This analysis identified the 15 most commonly used and emerging techniques, showing a shift toward more sensitive and innovative methods in microplastic studies. This novel Regex-Llama approach, introduced here for the first time, provides a scalable methodology applicable to various searches, including the analysis of pollutants in environmental science, the evaluation of material degradation in materials engineering, and the assessment of the toxicological effects of micro-contaminants on public health. This strategy facilitates environmental evaluations and aids in formulating pollution reduction measures, addressing many difficulties across several interesting fields.